THE EFFECTS OF INTEGRATED MARKETING COMMUNICATION ON ORGANIZATIONAL PERFORMANCE FOR ONE TAMBON ONE PRODUCT : CASE STUDY FOR NAKHON PATHOM PROVINCE, THAILAND - ISARI PAIROA1; SAKSIT RACHRUK2, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The overall goal of this research was to determine the impact of integrated marketing communication on organizational performance in Thailand for One Tambon One Product case study for nakhon pathom province, Thailand. The following precise aims led the research. To assess how direct personal selling affects performance of One Tambon one product case study for nakhon pathom province, Thailand, to determine the impact of advertising on performance of One Tambon one product case study for nakhon pathom province, Thailand, to determine the impact of sales promotion on performance of One Tambon one product case study for nakhon pathom province, Thailand, and to determine the impact of advertising on performance of One Tambon one product case study for nakhon pathom province, Thailand. This study uses a quantitative technique using a sample of 400 smartphone users as participants. The questionnaire was given to each responder personally by the researcher. This study's quantitative data was examined using descriptive statistics and a statistical software for social sciences (SPSS). To profile sample characteristics and key patterns emerging from the data, descriptive statistics such as mean, frequency, standard deviation, and percentages are used. To examine the relative relevance of each of the four factors in relation to the success of the One Tambon One product case study for nakhon pathom province, Thailand, a multivariate regression model was used. According to the findings, integrated marketing communication (IMC) has a favorable influence on the performance of One Tampon one product in Thailand, with advertising having the most impact, followed by sales promotions, and personal selling having the least impact. As a result, the Company must make the most of social media tools like Twitter, Facebook, and blogs to engage with, inform, and encourage input from a hitherto underserved target group. For client retention and to strengthen strong customer relationships, the organization should continue to connect with key customers one-on-one. As a vehicle for achieving the Company's business objectives, IMC must remain an intrinsic part of senior management's business strategy.